Pengembangan Modul Pembelajaran Berbasis QR Code sebagai Penunjang Keterampilan Gerak Dasar Permainan Bolavoli bagi Siswa Kelas VIII SMP Negeri 1 Jombang - Ossa Viantina; Basuki Basuki; Risfandi Setyawan; Guntum Budi Prasetyo (MODELING: Jurnal Program Studi PGMI, 2023)
Based on the results of the needs analysis conducted at SMPN 1 Jombang, multimedia technology-based learning media is needed in learning volleyball basic movement skills to improve learning outcomes and student interest in learning. So this study aims to develop learning media in the form of learning modules using QR Code. The research method used is R&D "Research and Development". The population of this study amounted to 130 students. The research instrument used a questionnaire for four validators, and a student questionnaire. The data analysis technique used quantitative descriptive with percentage score results. The average value of the evaluation results from expert 1 is 71.2% (valid), expert 2 79.8% (very valid), expert 3 80.3% (very valid), and expert 4 85% (very valid) . The results of the test to students increased in value from 69.6% to 95.2% (cognitive) and increased from 47.7% to 76.8% (Psychomotor). From these data, it can be concluded that the development of the basic volleyball skills learning module using QR Code can be used as a learning medium for class VIII SMP/MTs/equivalent students.